Prospects of Fungus-Based Biopesticides for Management of Insect Vectors of Maize Lethal Necrosis Disease - Kiarie, S.; Nyasani, J. O.; Gohole, L.; Maniania, N.; Sevgan, S. (African Journal of Education,Science and Technology (AJEST), 2020)
Maize, Zea mays L., production in Kenya is constrained by both biotic and abiotic factors. For instance, maize lethal necrosis (MLN) was first reported in Bomet County in 2011 and has since spread to other maize growing areas. In Kenya, MLN is reported to be caused by a co-infection of maize plant by Maize chlorotic mottle virus (MCMV) and Sugarcane mosaic virus (SCMV). Since this disease is new to Africa, there is little information about management of its insect vectors. To develop management strategies for MLN insect vectors, a field experiment was conducted using fungus-based biopesticides, Metarhizium anisopliae (MA) and Trichoderma asperellum (TA), and Nurelle*D 50/500EC (NuD) insecticide. Seven treatment were used: 1) untreated plot; 2) soil application of TA with foliar sprays of NuD; 3) soil application of TA with foliar spray of MA; 4) soil application of TA with foliar spray of MA and NuD; 5) foliar spray of NuD alone; 6) foliar sprays of MA alone; 7) soil application of TA alone. Data on MLN insect vectors were collected bi-weekly. Single and combined NuD application with biopesticides reduced population densities of various thrips species up to 5.1 folds compared to the controls. At peak period for aphid infestation, plots receiving single and combined application of TA and MA and treatment combination of TA, MA and NuD outperformed those receiving single and combined application of NuD with TA in reducing population of R. maidis. This study demonstrated that combined use of biopesticides and NuD can effectively manage MLN vectors.